Edukasi Keselamatan Dan Kesehatan Kerja Pada Pelaku Usaha Di Lingkungan UPPKA Layang-Layang - Hanani , Atidira Dwi; Yustini, Tien (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Efforts to Increase Acceptor Family Income Layang-Layang is one of the community groups in Palembang City in which there are a number of business actors who develop various types of businesses in order to improve the family economy. One of the challenges that business actors are still facing today is how to increase productivity, as well as improve Occupational Safety and Health (OSH) in the workplace. The lack of application of OSH in businesses is caused by a lack of access to information and limited training opportunities. Therefore, this community service is carried out for business actors in the UPPKA Layang-Layang which aims to provide OSH management education to assist entrepreneurs and workers in improving OSH and productivity in the workplace. Occupational safety and health education activities for business actors in the UPPKA Layang-Layang run smoothly and were attended by 20 participants. The results of the knowledge measurement with the questionnaire showed an increase in participants' knowledge about Occupational Safety and Health by 60% between before and after the education of participants. Business actors were also quite active in providing responses during the discussion process. The suggestions for further activities are to conduct training on financial management for business actors and also simulations related to emergency response systems for the safety of business actors. Similar community service activities can be carried out routinely either at the same location or at different locations. With good knowledge of OSH, business actors can implement OSH in the workplace and increase business productivity in the UPPKA Layang-Layang Environment.